Perancangan Sistem Penggajian Karyawan Pada PT. Mustika Bahari - Kania, Raden; Sulsiah, Sulsiah; Haerani, Anggi (Teknik Informatika Fakultas Ilmu Komputer, 2023)
In the age of information technology as it now has made humans. Entering a new era, namely the information age that demands everything running fast, CV. Mustika Bahari is a company engaged in the industrial sector that has not implemented a computerized system so that existing payroll information for new employees can not be fulfilled optimally. To get information, the data processing. Slow can result in slow presentation, a problem that exists in CV. Mustika Bhari than the finance and admiistartion departemen. The design uses the waterfall method, data flow, and entity relationship diagram. The employee payroll system, because this computerized payroll information system can change work that was previously done manually and seems to take a long time to provide information and make a decision in doing attendance employee hiring employees